Review of the comb-tailed spider genus Hahnia C.L. Koch 1841 (Hahniidae) from Gaoligong Mountains in Yunnan, China - Huang, Gui-Qiang; Zhang, Zhi-Sheng; Liu, Ying-Hong (Zootaxa, 2017)
Gaoligong Mountains in Yunnan, China are famous for the biodiversity and are part of Indo-Burmese hotspot. We present a review on the comb-tailed spider genus Hahnia C.L. Koch 1841 based on newly collected specimens. Four new species of Hahnia are described: H. biapophysis sp. nov. (male), H. dongi sp. nov. (male), H. subsaccata sp. nov. (male, female) and H. wangi sp. nov. (male, female). Two additional known species are redescribed: H. himalayaensis Hu & Zhang, 1990 and H. musica Brignoli, 1978. Hahnia musica previously known from Bhutan is recorded from China for the first time. Photos of habitus and genitalia of all species and additionally illustrations of new species are given.